1999
DOI: 10.1093/alcalc/34.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nicotinic acetylcholine receptors in the regulation of alcohol drinking in Wistar rats

Abstract: The aim of the present study was to determine if nicotinic acetylcholine receptors (nAChRs) might be involved in the regulation of alcohol intake by Wistar rats. A non-selective nAChR agonist, nicotine, and a non-competitive nAChR antagonist, mecamylamine, were tested in alcohol-preferring Wistar rats maintained on a limited access (4 h/24 h) to ethanol (10%, v/v). In addition, the effects of nicotine and mecamylamine on intake of standard laboratory chow were studied in a separate control experiment. Nicotine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Moreover, Le and colleagues (2003), showed that nicotine-induced enhancement in ethanol operant selfadministration depended on the dose and time after the last nicotine injection. However, nicotine pre-treatment has also been associated with decreased operant self-administration of ethanol [36][37][38]. The reasons for these different results may be due to the nicotine withdrawal period, schedule of administration, or dose of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Le and colleagues (2003), showed that nicotine-induced enhancement in ethanol operant selfadministration depended on the dose and time after the last nicotine injection. However, nicotine pre-treatment has also been associated with decreased operant self-administration of ethanol [36][37][38]. The reasons for these different results may be due to the nicotine withdrawal period, schedule of administration, or dose of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has been reported to enhance the function of naturally expressed α4β2 nAChRs and to inhibit the activity of naturally expressed α7 nAChRs (Narahashi et al, 1999). Furthermore, activation of nAChRs was reported to selectively reduce alcohol consumption in outbred Wistar rats (Dyr et al, 1999), while mutations in transmembrane domains of α2 channel subunits can enhance actions of alcohols on neuronal nicotinic receptors (Borghese et al, 2002). …”
Section: Human Alcohol-responsive Mirnas Neurotransmitter Signalingmentioning
confidence: 99%
“…However, the results have been mixed, with studies also reporting that nicotine has no effect or even decreases ethanol self-administration [2325]. We will review the evidence that nicotine increases ethanol self-administration by highlighting studies that use operant reinforcement to study the interaction.…”
Section: Introductionmentioning
confidence: 99%